2015
DOI: 10.1155/2015/687094
|View full text |Cite
|
Sign up to set email alerts
|

ZnO-PLLA Nanofiber Nanocomposite for Continuous Flow Mode Purification of Water from Cr(VI)

Abstract: Nanomaterials of ZnO-PLLA nanofibers have been used for the adsorption of Cr(VI) as a prime step for the purification of water. The fabrication and application of the flexible ZnO-PLLA nanofiber nanocomposite as functional materials in this well-developed architecture have been achieved by growing ZnO nanorod arrays by chemical bath deposition on synthesized electrospun poly-L-lactide nanofibers. The nanocomposite material has been tested for the removal and regeneration of Cr(IV) in aqueous solution under a “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…This is due to the increase in adsorption active sites because of introduction of amine functional groups onto GO surface. We have also compared the maximum adsorption capacity value of NH 2 -GO/ZnO-ZnFe 2 O 4 with the other reported adsorbents for Cr­(VI) removals and represented in Table S2. ,, It is observed that NH 2 -GO/ZnO-ZnFe 2 O 4 is an effective adsorbent toward the adsorption of Cr­(VI).…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the increase in adsorption active sites because of introduction of amine functional groups onto GO surface. We have also compared the maximum adsorption capacity value of NH 2 -GO/ZnO-ZnFe 2 O 4 with the other reported adsorbents for Cr­(VI) removals and represented in Table S2. ,, It is observed that NH 2 -GO/ZnO-ZnFe 2 O 4 is an effective adsorbent toward the adsorption of Cr­(VI).…”
Section: Resultsmentioning
confidence: 99%
“…1 Concerning the strategies for the purification of water contaminated with heavy metals, the use of systems based on polymer membranes has been extensively preferred due to suitable mechanical performance that these materials provide for highpressure processes and their versatility of thermal and chemical properties. [18][19][20][21][22][23][24] Three main approaches for fabricating polymer/ZnO fibrous membranes have been explored: (1) electrospinning of a polymer solution containing ZnO nanoparticles, 22,[25][26][27][28] (2) deposition of ZnO nanoparticles onto electrospun membranes by several methods, namely, impregnation, electrospraying, or similar techniques, [29][30][31][32][33][34][35] and in a minor extent (3) coaxial electrospinning. [2][3][4] In this context, electrohydrodynamic techniques provide excellent approaches for the design of nanofibrous polymeric membranes with tailored morphology.…”
Section: Introductionmentioning
confidence: 99%
“…The photocatalytic decomposition was monitored on various organic pollutant dyes, such as methylene blue, monocrotophos, and diphenylamine under illumination with UV light using this highly flexible hierarchical nanostructure. The same electrospun ZnO-poly-L-lactide nanofibers photocatalysts have been used for the adsorption of Cr(VI) as a crucial step for water purification by Burks et al [13].…”
Section: Introductionmentioning
confidence: 99%